ChemInform Abstract: Direct Synthesis of 2, 3‐Diaryloxirane‐2, 3‐dicarbonitriles from Aroyl Chlorides Using Potassium Hexacyanoferrate(II) as an Eco‐Friendly Cyanide Source. Issue 11 (8th March 2013) - Li, Zheng; Xu, Jun; Niu, Pengxian; Liu, Chenhui; Yang, Jingya
Abstract The important synthetic intermediates can be prepared within a relatively short time.